Alcohol use during pregnancy in post-conflict northern Uganda: pregnant women's experiences and provider perceptions - Apophia Agiresaasi; Nazarius Mbona Tumwesigye; Elizabeth Nabiwemba; Juliet Kiguli; Gakenia Wamuyu Maina; Goretti Nassanga (BMC, 2021)
Abstract Background Alcohol use during pregnancy has been associated with several birth defects and developmental disabilities generally known as Fetal Alcohol Spectrum Disorders (FASD). Contextual in-depth understanding on why women drink while pregnant is scarce. For this reason, we explored pregnant women's experiences, knowledge, attitudes as well as provider perceptions regarding prenatal alcohol consumption to inform interventions meant to address alcohol-exposed pregnancies in post-conflict settings. Methods In the months of May and June 2019, 30 in-depth interviews were conducted with pregnant mothers who reported maternal alcohol use during pregnancy. In addition 30 Key informant interviews were carried out with health workers providing Antenatal Care services (ANC) in health facilities in Gulu, Kitgum and Pader districts in Northern Uganda. Data was recorded, transcribed and subjected to thematic content analysis. Results Women reported diverse views regarding maternal alcohol use during pregnancy. Whereas some felt it was favourable, others had misgivings about it. There was marked variability in knowledge on dangers of drinking during pregnancy. In this study, women reported that they found themselves in alluring situations that predisposed them to drinking alcohol. These included brewing alcohol as a source of livelihood, pregnancy-induced craving for alcohol, and participation in cultural festivities that are characterised by eating and drinking alcohol. Nonetheless, women who consume alcohol during pregnancy were not held in high esteem in the Acholi communities. Various prevention interventions reportedly existed in communities to address alcohol use during pregnancy including ANC health education, public debates, radio talk shows, community health worker group and individual counselling, and local council by laws. Conclusions and recommendations Pregnant mothers in post-conflict northern Uganda regard alcohol as a remedy to some of the social, economic and health challenges they face. Hence they continue drinking even during pregnancy because of the existing socio-cultural norms that promote it. The findings of this study demonstrate a need for sensitising communities in which pregnant women live so they can provide a supportive environment for mothers to abstain from alcohol consumption during pregnancy. Health care providers should ensure pregnant women consistently receive accurate and honest messages on the dangers of drinking during pregnancy so they can make informed decisions.